(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The owners of Kabayan Pares Mami decided to start a small business located near a school, factory, and wet market. It is a great location to start a business. Kabayan Pares Mami faces many different problems and complaints from their customers where they address the small portion of the product and the limited seats available. These instances led to unsatisfied customers. The researchers made a survey questionnaire for the customers to fill out where they can give suggestions for the improvement of the business. Based on the results, the significant difference in the level of customer satisfaction between employed and unemployed customers of Kabayan Pares Mami revealed that there is no significant difference in the level of customer satisfaction between employed customers and unemployed customers in terms of Serving Time (t-stat value of 0.458831 and 0.67018 with p-value) respectively leads to accepting the nulled hypothesis while the level of customer satisfaction between employed customers and unemployed customers in terms of Completeness of Orders has significant difference (t-stat value of 5.962848 and 0.00397 with p-value) which leads to rejecting the nulled hypothesis. Lastly, the level of customer satisfaction between employed customers and unemployed customers in terms of Hospitality found that there is no significant difference (t-stat value of -0.693334 and 0.52625 with p- value) that leads to accepting the nulled hypothesis. The findings show that the majority of the respondents are 18-29 years old, male and single. The level of customer satisfaction in Kabayan Pares Mami between two groups of respondents in terms of serving time, completeness of orders, and hospitality is “Highly Satisfied.” There is no significant difference between an assessment of two groups of respondents as to the cited variables. The biggest challenge encountered by the customers of Kabayan Pares Mami is the Limited seats available. The researchers propose guidelines and recommendations to help Kabayan Pares Mami enhance the level of their customer satisfaction to retain and acquire more customers.